Diagnosis and Characterization of DSM-5 Nonsuicidal Self-Injury Disorder Using the Clinician-Administered Nonsuicidal Self-Injury Disorder Index. (October 2015) - Gratz, Kim L.; Dixon-Gordon, Katherine L.; Chapman, Alexander L.; Tull, Matthew T.
Despite the inclusion of nonsuicidal self-injury disorder (NSSID) in the DSM-5, research on NSSID is limited and no studies have examined the full set of DSM-5 NSSID diagnostic criteria. Thus, this study examined the reliability and validity of a new structured diagnostic interview for NSSID (the Clinician-Administered NSSI Disorder Index; CANDI) and provides information on the clinical characteristics and features of DSM-5 NSSID. Data on the interrater reliability, internal consistency, and construct validity of the CANDI and associated characteristics of NSSID were collected in a community sample of young adults ( N = 107) with recent recurrent NSSI (≥10 lifetime episodes of NSSI, at least one episode in the past year). Participants completed self-report measures of NSSI characteristics, psychopathology, and emotion dysregulation, as well as diagnostic interviews of borderline personality disorder (BPD) and lifetime mood, anxiety, and substance use disorders. The CANDI demonstrated good interrater reliability and adequate internal consistency. Thirty-seven percent of participants met criteria for NSSID. NSSID was associated with greater clinical and diagnostic severity, including greater NSSI versatility, greater emotion dysregulation and psychopathology, and higher rates of BPD, bipolar disorder, posttraumatic stress disorder, social anxiety disorder, and alcohol dependence. Findings provide support for the reliability, validity, and feasibility of the CANDI.